Analisis Faktor-faktor Yang Mempengaruhi Kejadian Bayi Berat Lahir Rendah di PMB Andina Palembang - Suci Sulistyorini (IKesT Muhammadiyah Palembang, 2022)
One of the indicators of a country's success in improving public health is by decreasing the infant mortality rate (IMR). The most common cause of neonatal death is low birth weight (LBW). 2017 shows AKN of 15 per 1,000 live births, IMR of 24 per 1,000 live births, and AKABA 32 per 1,000 live births. The incidence of LBW is still quite high in the city of Palembang, Based on data from the Independent Practice Report of Midwife Andina Primitasari Palembang, it was found that the incidence of LBW in 2018 was 10 events, in 2019 11 events and in 2020 the period January 1 to May 30 totaled 11 events. This study aims to analyze the factors that influence the incidence of low birth weight babies in PMB Andina Primitasari Palembang. The design of this study used an analytical survey method with a case control research design. The population in this study were all newborns who were recorded as being born in PMB